Comparison of a Supraglottic Airway Device (v-gel®) with Blind Orotracheal Intubation in Rabbits - Engbers, Sarah; Larkin, Amy; Rousset, Nicolas; Prebble, Melanie; Jonnalagadda, Mahesh; Knight, Cameron G.; Pang, Daniel S. J. (Frontiers in Veterinary Science, 2017)
Introduction Achieving a secure airway in rabbits is generally considered more difficult than in cats or dogs. Their relatively large tongue, small oropharyngeal cavity and glottis limit direct visualization. A rabbit-specific supraglottic airway device (SGAD) may offer benefits over blind orotracheal intubation. Materials & methods Fifteen adult New Zealand white rabbits were randomised to SGAD or orotracheal intubation (ETT). All animals were sedated with dexmedetomidine (0.1 mg kg-1 IM) and midazolam (0.5 mg kg-1 IM), followed by induction with alfaxalone (0.3 mg kg-1 IV). Two CT scans of the head and neck were performed, following sedation and SGAD/ETT placement. The following were recorded: time to successful device insertion, smallest cross-sectional airway area, airway sealing pressure and histological score of tracheal tissue. Data were analysed with a Mann-Whitney test. Results Two rabbits were excluded following failed ETT. Body masses were similar (ETT; n = 6, 2.6 [2.3 - 4.5] kg. SGAD; n = 7, 2.7 [2.4 - 5.0] kg). SGAD placement was significantly faster (33 [14 - 38] seconds) than ETT (59 [29-171] seconds). Cross-sectional area was significantly reduced from baseline (12.2 [6.9 - 13.4] mm2) but similar between groups (SGAD; 2.7 [2.0 - 12.3] mm2, ETT; 3.8 [2.3 - 6.6] mm2). In the SGAD group, the device tip migrated into the laryngeal vestibule in 6/7 rabbits, reducing the cross-sectional area. ETT airway seals were higher (15 [10 - 20] cmH2O), but not significantly (SGAD; 5 [5 - 20] cmH2O, p = 0.06). ETT resulted in significantly more mucosal damage (histological score 3.3 [1.0 - 5.0]), SGAD; 0.67 [0.33 - 3.67]). Conclusions The SGAD studied was faster to place and caused less damage than orotracheal intubation, but resulted in a similar cross-sectional area.